Perioperative Care of Free Flap Patients - Vincent, Aurora; Sawhney, Raja; Ducic, Yadranko (Seminars in Plastic Surgery, 2019)
Microvascular free tissue transfer is an indispensable reconstructive option in head and neck reconstruction. Flap failure is relatively rare, but it is nonetheless very morbid and psychologically devastating to patients when it does occur. Further, complications after free tissue transfer to the head and neck remain common. There are numerous ongoing debates about various facets of preoperative, intraoperative, and postoperative care of patients undergoing free flap reconstruction of the head and neck, all ultimately searching for the optimal treatment algorithm to further improve flap success, minimize complications, and maximize patient outcomes. Herein, the authors review current literature surrounding optimal preoperative nutritional support, intraoperative vasopressor use, perioperative fluid management, use of antithrombotic agents, antibiotic use, and other facets of the care of head and neck free flap patients to provide a guide to surgeons.
Keywords: free tissue transfer; perioperative care; head and neck reconstruction